Witness to Marvels : Sufism and Literary Imagination. - Stewart, Tony K. (Islamic Humanities Series, 2019)
A free open access ebook is available upon publication. Learn more atwww.luminosoa.org. There is a vast body of imaginal literature in Bengali that introduces fictional Sufi saints into the complex mythological world of Hindu gods and goddesses. Dating to the sixteenth century, the stories--pir katha--are still widely read and performed today. The events that play out rival the fabulations of the Arabian Nights, which has led them to be dismissed as simplistic folktales, yet the work of these stories is profound: they provide fascinating insight into how Islam habituated itself into the cultural life of the Bangla-speaking world. In Witness to Marvels, Tony K. Stewart unearths the dazzling tales of Sufi saints to signal a bold new perspective on the subtle ways Islam assumed its distinctive form in Bengal.